Evaluating Boil Water Advisory Policies and Practices: Health Outcomes in Hong Kong - Simpson Shiu Chung Tam; Ben Yuk-fai Fong (ACHSM, 2024)
Boiling water (BW) is a common global practice, especially in Asia, for ensuring safe drinking water, though it does not remove chemical contaminants. The World Health Organisation recommends BW as an emergency measure against microbial contamination. In Hong Kong, the Water Supplies Department ensures water quality through strict regulations and extensive monitoring. Comparisons with Norway and Canada reveal effective practices such as water safety planning and risk-based advisories. Norway mandates water safety planning and uses messaging notifications for water advisories, ensuring high compliance, while Canada issues site-specific BW advisories based on risk assessments. Hong Kong faces unique challenges, such as a warm climate and complex building infrastructure, which impact water quality. Many buildings lack proper maintenance, leading to potential health risks and necessitating regular maintenance. Health management, public health education and expert guidance are essential for promoting efficient practices and ensuring safe drinking water.